2018
DOI: 10.12928/jp.v1i2.363
|View full text |Cite
|
Sign up to set email alerts
|

PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN LIMBAH KULIT BUAH NANAS (ananas comosus L. Merr) MENJADI SYRUP KAYA VITAMIN DI KECAMATAN PAYARAMAN

Abstract: Kecamatan Payaraman merupakan suatu daerah yang memiliki potensi yang besar dalam bidang perkebunan nanas dan dapat menjadi komoditas unggulan daerah. Penggunaan tanah Payaraman sebagian besar diperuntukan untuk pertanian, padi, nanas, dan karet sedangkan sisanya untuk tanah kering yang merupakan bangunan dan fasilitas-fasilitas lainnya. Dengan luas perkebunan karet yang dimanfaatkan sebagai lahan tanam nanas. Banyaknya hasil perkebunan nanas yang dihasilkan membuat nanas menjadi komoditas unggulan dan mencuku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The higher this production, the more waste is generated. Consumption can produce peel waste by 34.61% (Syauqi, 2020), therefore the utilization needs to be optimally carried out to reduce the amount and increase the economic value of the waste (Susanti, 2013;Mahmud, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher this production, the more waste is generated. Consumption can produce peel waste by 34.61% (Syauqi, 2020), therefore the utilization needs to be optimally carried out to reduce the amount and increase the economic value of the waste (Susanti, 2013;Mahmud, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A literature search by Rachmawati (2021), showed the use of banana and pineapple peels as liquid organic fertilizers is following quality standards (Rachmawati, 2021). Novia et al, 2022 showed that the combined banana and pineapple peel extracts do not have a toxic effect, hence they are safe to use (Novia, 2022). According to Hiqbar et al, (2022), based on the combination of banana and pineapple peels (3:1) by in vivo test on rats, potassium levels in the blood are normal (Hiqbar, 2022).…”
Section: Introductionmentioning
confidence: 99%